The Effect of DMR on Students Mathematical Problem Solving Ability and Self Efficacy - Pratiwi, Dona Dinda; Selvianti, Devara (Journal of Learning Improvement and Lesson Study, 2023)
Problem solving ability and self efficacy are two important aspects that must be owned in order to learn mathematics well. This study aims to determine the effect of the Multi Representation Discourse (DMR) learning model on mathematical problem solving abilities and self efficacy learners. This type of research uses a quasy experiment using a posttest only control group design. The population in the study included all grade VIII junior high school students in the city of Bandar Lampung. The sampling technique used was cluster random sampling, with 50 students as respondents. The hypothesis test used in this study is manova. Based on the results of the study that the DMR model influences students' problem-solving abilities and self-efficacy, the use of the DMR learning model can improve students' mathematical problem-solving abilities, and students' self-efficacy can be increased using the DMR learning model.